RESPON PEMBUNGAAN BEBERAPA KULTIVAR ANTHURIUM BUNGA POTONG TERHADAP APLIKASI GA3 - BUDIARTO, K.; WURYANINGSIH, S. (AGRITROP; Vol. 26, No. 2 Juni 2007, 2012)
Anthurium is one of popular ornamental cut flowers in the world. Some constraints were revealed during production process due to the low plant productivity. Stimulating the plant to undergo earlier reproductive stage for producing more flowers was investigated. The application of growth regulator was predicted to have more desirable effects on this case as far as these concerned. The research was then, conducted to find out the effects of foliar spray of GA3 on the flowering response of several anthurium cultivars. The experiment was carried out at The Indonesian Ornamental Crops Research Institute from March to August 2005. A Randomized Completely Blocked Design (RCBD) with 7 replications was used. The first factor was GA3 concentration i.e. 0 (control), 500, 1000, 1500 and 2000 ppm, while the second factor was anthurium cultivars namely cv. Tropical, Kaumana and Safari. Results of the experiment showed that the application of GA3 hastened flower initiation and number of flowers per plant compared to the intact plant. However, the application of more than 500 ppm have no significant desirable effects. Stalk length and diameter decreased with the application of GA3 and more undesirable effects on stalk diameter was observed under GA3 higher than 1000 ppm. Cv. Tropical showed earlier flowering response and produced more flower than cv. Kaumana and Safari. However, this cultivar has the least stalk length and diameter. The highest stalk length and diameter was observed in cv. Safari.
Keywords: Anthurium andreanum, GA3 (Gibberellic acids), flower induction